2020
DOI: 10.1016/j.celrep.2020.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Resist Mechanical Destruction in Circulation via RhoA/Actomyosin-Dependent Mechano-Adaptation

Abstract: Highlights d Cancer cells from primary tumors are resistant to fluid shear stress (FSS) d Resistance to FSS is a physiological, mechano-adaptive response in cancer cells d Cancer cells respond to FSS by activating the RhoA-myosin II axis and formins d Myosin II activity protects CTCs from hemodynamic forces in in vivo assays Authors

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 62 publications
(57 reference statements)
2
70
0
1
Order By: Relevance
“…In our recent study we demonstrated that exposure to FSS in vitro results in the activation of ras homolog family member A (RHOA) in cancer cells (Figure 1). 10 FSS exposure also led to both a formin-dependent increase in cortical F-actin levels and an increase in activation of myosin, consistent with the activation of these cytoskeletal master regulators, that prevents damage to the plasma membrane induced by FSS (Figure 1). 10 Inhibiting the mechano-adaptive response through the RHOA-actomyosin network led to an increase in the fraction of cells destroyed by both in vitro applied FSS and hemodynamic FSS, a decrease in the CTC burden of orthotopically injected mice, and a delay in the onset of metastatic disease using an experimental metastasis model.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…In our recent study we demonstrated that exposure to FSS in vitro results in the activation of ras homolog family member A (RHOA) in cancer cells (Figure 1). 10 FSS exposure also led to both a formin-dependent increase in cortical F-actin levels and an increase in activation of myosin, consistent with the activation of these cytoskeletal master regulators, that prevents damage to the plasma membrane induced by FSS (Figure 1). 10 Inhibiting the mechano-adaptive response through the RHOA-actomyosin network led to an increase in the fraction of cells destroyed by both in vitro applied FSS and hemodynamic FSS, a decrease in the CTC burden of orthotopically injected mice, and a delay in the onset of metastatic disease using an experimental metastasis model.…”
supporting
confidence: 55%
“…10 FSS exposure also led to both a formin-dependent increase in cortical F-actin levels and an increase in activation of myosin, consistent with the activation of these cytoskeletal master regulators, that prevents damage to the plasma membrane induced by FSS (Figure 1). 10 Inhibiting the mechano-adaptive response through the RHOA-actomyosin network led to an increase in the fraction of cells destroyed by both in vitro applied FSS and hemodynamic FSS, a decrease in the CTC burden of orthotopically injected mice, and a delay in the onset of metastatic disease using an experimental metastasis model. 10 Importantly, we also showed that FSS resistance is a property of cancer cells directly isolated from genetically-engineered mouse primary tumors and patient-derived xenografts, demonstrating that FSS resistance observed in cancer cells is not a product of in vitro culture or metastatic selection.…”
supporting
confidence: 55%
See 3 more Smart Citations